2015
DOI: 10.1111/bjd.14155
|View full text |Cite
|
Sign up to set email alerts
|

High neutrophil to lymphocyte ratio measured before starting ipilimumab treatment is associated with reduced overall survival in patients with melanoma

Abstract: SummaryBackground There is an unmet need to identify markers predictive of response to ipilimumab in patients with melanoma because the number of responders to ipilimumab is low and its cost is very high. An increase in absolute lymphocyte count (ALC) or low neutrophil/lymphocyte ratio (NLR) just before the third infusion has been reported to be associated with better overall survival (OS). Objectives Our aim was to determine whether NLR measured before the first infusion was associated with OS. Patients and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
123
3
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(134 citation statements)
references
References 30 publications
6
123
3
2
Order By: Relevance
“…Also, the separate analysis of patients without CNS metastases did not change these results. Baseline NLR represents an independent prognostic factor for cancer immunotherapy outcomes, and high values (cutoff 4 or 5) correlate with worse treatment responses (32,45). In our study, we did not find significant differences of baseline NLR values between the two treatment groups.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…Also, the separate analysis of patients without CNS metastases did not change these results. Baseline NLR represents an independent prognostic factor for cancer immunotherapy outcomes, and high values (cutoff 4 or 5) correlate with worse treatment responses (32,45). In our study, we did not find significant differences of baseline NLR values between the two treatment groups.…”
Section: Discussioncontrasting
confidence: 54%
“…A cutoff NLR value of 4, as previously established, was set in order to separate prognostic groups (32).…”
Section: Measures Of Immune Responsementioning
confidence: 99%
“…However, whether NLR remains a general prognostic factor or predictive for ipilimumab benefit in the metastatic setting remains unclear. Moreover, Zaragoza confirmed that an elevated NLR (≥4) before initiating ipilimumab treatment in patients with metastatic melanoma to be an independent prognostic indicator of poor survival [26]. Additionally, treatments aimed at abrogating the suppressive function of neutrophils and other myeloid-derived cells could shift the balance in favor of immune system dominance over tumor progression.…”
Section: Discussionmentioning
confidence: 99%
“…• A high neutrophil/lymphocyte ratio correlated with poor patient outcome after immunotherapy whereas elevated eosinophil counts may be associated with improved outcome in melanoma patients treated with anti-CTLA-4 antibody [9]…”
Section: Immuno-oncologymentioning
confidence: 99%